2007
DOI: 10.1016/j.ijsu.2006.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative neutrophil–lymphocyte ratio predicts complications following colorectal surgery

Abstract: NLR > or =9.3 on the first post-operative day is associated with an increased risk of complications. This simple derivation of routinely available data helps to identify patients at high-risk of complications, allowing targeted preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 12 publications
2
75
0
2
Order By: Relevance
“…There is evidence that NLR is a good prognostic factor in other cancers, such as colorectal cancer, 14 and it has also been identified as a predictor for postoperative complications following colorectal surgery. 15 In this study, both NLR and CA19.9-bilirubin ratio were found to have high positive predictive values for unresectability (88.9 and 76.5%, respectively). Therefore, both results could have an integral role in the staging process for pancreaticoduodenectomy.…”
Section: Discussionsupporting
confidence: 49%
“…There is evidence that NLR is a good prognostic factor in other cancers, such as colorectal cancer, 14 and it has also been identified as a predictor for postoperative complications following colorectal surgery. 15 In this study, both NLR and CA19.9-bilirubin ratio were found to have high positive predictive values for unresectability (88.9 and 76.5%, respectively). Therefore, both results could have an integral role in the staging process for pancreaticoduodenectomy.…”
Section: Discussionsupporting
confidence: 49%
“…NLR can easily be calculated by the ratio of neutrophils to lymphocytes in peripheral blood.It is a very simple and cheap method when compared with the other inflammatory cytokines including IL-6, IL-1b, and TNF-a [8]. In previous studies, increased NLR was demonstrated in cardiovascular and cerebrovascular diseases such as hypertension, unstable angina pectoris, myocardial infarction, transient ischemic attacks and stroke [9][10][11][12][13]. Moreover NLR has been found as a valuable index for predicting clinical outcomes in oncology [14][15][16][17] and inflammatory diseases such as Alzheimer, ulcerative colitis and appendicitis [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…NLR > 5 values were found to be predictive (6,10). Cook et al (11) found that postoperative NLR predicted complications following colorectal surgery. In that study, NLR > 9.3 on the first postoperative day correlated with an increased risk of complications.…”
Section: Discussionmentioning
confidence: 99%